Rubber composition and tire

By mixing inorganic fiber materials and coupling agents in the rubber composition, the existing rubber composition has the lack of fracture strength and the opposite sex, and achieves efficient reinforcement performance and improved ride comfort and manipulation stability sex.

CN114585675BActive Publication Date: 2025-01-28SUMITOMO RUBBER INDUSTRIES LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202080073574.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-11-11
Filing Date
2020-10-19
Publication Date
2025-01-28
Estimated Expiration
2040-10-19

AI Technical Summary

Technical Problem

The existing rubber compositions have shortcomings in improving fracture strength and anisotropy, especially when the dispersion state of the fiber materials is poor, it is difficult to obtain sufficient reinforcement performance, resulting in the inability to meet the market demand for riding comfort and vibration.

Method used

By mixing inorganic fiber materials and coupling agents, a rubber composition that contains rubber components, inorganic fiber materials and coupling agents to ensure the uniform dispersing and orientation of fiber materials in the rubber matrix, thereby improving the broken strength and each each To the opposite sex.

Benefits of technology

The high -broken strength and the opposite sex of the rubber composition are realized, and the ride comfort and manipulation stability of the internal components of the tire are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003605484250000071
    Figure BDA0003605484250000071
  • Figure BDA0003605484250000081
    Figure BDA0003605484250000081
  • Figure BDA0003605484250000091
    Figure BDA0003605484250000091
Patent Text Reader

Abstract

A rubber composition is provided, which includes a rubber component, an inorganic fiber material and a coupling agent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a rubber composition containing an inorganic fiber material, and a tire having an inner component formed of the rubber composition. Background Art

[0002] A technique for imparting modulus anisotropy to rubber by compounding a bio-derived nanomaterial (such as cellulose fiber) in a tire component is known (eg, Patent Document 1).

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: JP 5691463 B Summary of the invention

[0006] Problems to be solved by the present invention

[0007] It is believed that the rubber is strengthened by forming a network structure, and anisotropy is easily obtained in the fiber material. However, if the dispersion state of the fiber material in the rubber matrix is ​​poor, the fiber material will condense, it is difficult to obtain anisotropy, and it is impossible to obtain sufficient reinforcement performance for the rubber matrix, so it is believed that the breaking strength will also be reduced. In addition, the rubber composition containing conventional fiber materials has a high elastic modulus, and currently cannot fully meet the market demand value in terms of ride comfort and vibration.

[0008] An object of the present invention is to provide a rubber composition capable of achieving both breaking strength and anisotropy to a high degree.

[0009] Means of solving the problem

[0010] Through intensive studies, the present inventors have found that by compounding an inorganic fiber material and a coupling agent, a rubber composition that highly achieves both breaking strength and anisotropy can be obtained, thereby completing the present invention.

[0011] In other words, the present invention relates to:

[0012] [1] A rubber composition comprising a rubber component, an inorganic fiber material and a coupling agent.

[0013] [2] The rubber composition according to [1] above, wherein a ratio of a 100% modulus M100a in a grain direction to a 100% modulus M100b in a cross-grain direction (M100a / M100b) is 1.10 or more.

[0014] [3] The rubber composition of the above-mentioned [1] or [2], wherein the rubber composition further comprises carbon black (preferably 1 to 100 parts by mass, more preferably 5 to 80 parts by mass, relative to 100 parts by mass of the rubber component).

[0015] [4] The rubber composition according to any one of [1] to [3] above, further comprising a plasticizer (preferably 1 to 90 parts by mass, more preferably 3 to 70 parts by mass, per 100 parts by mass of the rubber component).

[0016] [5] The rubber composition described in any one of [1] to [4] above, wherein the rubber component contains an isoprene-based rubber (preferably 5% by mass or more, more preferably 10 to 90% by mass).

[0017] [6] The rubber composition according to any one of [1] to [5] above, wherein the coupling agent is a silane coupling agent.

[0018] [7] The rubber composition of any one of [1] to [6] above, wherein the rubber composition comprises 1 to 40 parts by mass of a coupling agent per 100 parts by mass of the rubber component.

[0019] [8] The rubber composition according to any one of [1] to [7] above, wherein the coupling agent is a silane coupling agent having a sulfide group.

[0020] [9] The rubber composition according to any one of [1] to [8] above, wherein the rubber composition further comprises carbon black (preferably 1 to 100 parts by mass, more preferably 5 to 80 parts by mass, relative to 100 parts by mass of the rubber component), wherein the carbon black has a cetyltrimethylammonium bromide adsorption specific surface area (CTAB) of 180 m 2 / g or less.

[0021]

[10] The rubber composition according to any one of [1] to [9] above, wherein the rubber composition contains 1 to 50 parts by mass of an inorganic fiber material relative to 100 parts by mass of the rubber component, wherein the inorganic fiber material has an average diameter D of 1.0 to 2000 nm, an average length L of 0.10 to 100 μm, and an aspect ratio L / D of 2 to 1000.

[0022]

[11] The rubber composition described in any one of [1] to

[10] above, wherein the inorganic fiber material is one or more inorganic fiber materials selected from magnesium sulfate fiber, calcium silicate fiber, potassium titanate fiber, aluminum borate fiber and sepiolite.

[0023]

[12] A tire interior component formed from the rubber composition described in any one of [1] to

[11] above.

[0024]

[13] A tire comprising the tire internal component described in

[12] above.

[0025]

[14] The tire described in

[13] above, wherein the tire is a tire for a passenger car.

[0026] Effects of the Invention

[0027] According to the present invention, by compounding an inorganic fiber material and a coupling agent, a rubber composition that achieves both high breaking strength and anisotropy is provided. In addition, a tire having a tire inner component formed of the rubber composition has improved ride comfort and handling stability in a well-balanced manner. DETAILED DESCRIPTION

[0028] Since the rubber composition of the present invention includes a rubber component, an inorganic fiber material and a coupling agent, it exhibits excellent breaking strength and anisotropy.

[0029] Although not intending to be bound by theory, the following may be considered as a mechanism by which the rubber composition of the present invention can exhibit excellent breaking strength and anisotropy.

[0030] By compounding an inorganic fiber material in a rubber composition, the modulus of the rubber can be anisotropic, but it is believed that the inorganic fiber material is difficult to disperse in the rubber component compared with fillers (such as carbon black). Therefore, the entire rubber matrix cannot be reinforced, and it is believed that it is difficult to obtain sufficient fracture strength and anisotropy. Here, by compounding a coupling agent with the inorganic fiber material, the dispersibility of the inorganic fiber material in the rubber matrix can be improved to reinforce the entire matrix, and the inorganic fiber material can be oriented in a uniform state, so it is believed that the anisotropy is also improved.

[0031] In the rubber composition (vulcanized rubber) of the present invention, from the perspective of excellent anisotropy, the value of the ratio of the 100% modulus M100a in the texture direction to the 100% modulus M100b in the transverse texture direction (M100a / M100b, which may be referred to as "modulus ratio" herein) as an anisotropy index is 1.10 or more, more preferably 1.15 or more, and further preferably 1.20 or more. On the other hand, the upper limit value of the modulus ratio is not particularly limited, but is generally 2.00 or less, and may be 1.80 or less, 1.60 or less, or 1.50 or less. By setting the modulus ratio to 1.10 or more, a flexible response in the transverse texture direction of the inorganic fiber material oriented in a highly dispersed state with the coupling agent can be achieved, the rigidity in the texture direction can be increased, and thus the responsiveness can be improved. In addition, in the present invention, "texture direction" refers to the rolling direction when a sheet is formed by extrusion or shearing, and "transverse texture direction" refers to the direction perpendicular to the texture direction.

[0032] In addition, when the rubber composition is used as a tire, the texture direction of the inorganic fiber can be any of the circumferential direction, radial direction and width direction of the tire, but from the perspective of improving ride comfort and handling stability in a good balance, it is preferably arranged along the tire circumferential direction. By orienting the inorganic fiber in the tire circumferential direction, a flexible response to input (vibration) from the vertical direction of the tire during rolling can be achieved; and by increasing the rigidity in the orientation direction (tire circumferential direction), the response to input during handling can be improved. Therefore, it is believed that ride comfort and handling stability can be improved in a good balance.

[0033] The procedure for manufacturing a tire (including the production of a rubber composition) according to one embodiment of the present invention will be described in detail below. However, the following description is an illustrative description for explaining the present invention and is not intended to limit the technical scope of the present invention to the description range. In addition, in this specification, the numerical range identified by "to" is intended to include the numerical values ​​at both ends.

[0034] <Rubber component>

[0035] Examples of the rubber component that can be used in the present invention include: diene rubbers such as isoprene rubber, styrene-butadiene rubber (SBR), butadiene rubber (BR), styrene-isoprene-butadiene rubber (SIBR), chloroprene rubber (CR) and acrylonitrile-butadiene rubber (NBR); non-diene rubbers such as ethylene-propylene-diene rubber (EPDM), butyl rubber (IIR) and halogenated butyl rubber (X-IIR), etc. These can be used alone or in combination of two or more. The rubber component may be a rubber component containing at least one selected from isoprene-based rubber, SBR and BR, may be a rubber component containing isoprene-based rubber, may be a rubber component containing isoprene-based rubber and BR, may be a rubber component consisting only of isoprene-based rubber and BR, may be a rubber component containing BR, may be a rubber component containing BR and SBR, may be a rubber component consisting only of BR and SBR, may be a rubber component containing isoprene-based rubber, SBR and BR, or may be a rubber component consisting only of isoprene-based rubber, SBR and BR.

[0036] The content of the diene rubber is preferably 60% by mass or more, more preferably 70% by mass or more, further preferably 80% by mass or more, and particularly preferably 85% by mass or more, based on 100% by mass of the rubber component. In addition, the rubber component may be a rubber component consisting only of a diene rubber.

[0037] (Isoprene rubber)

[0038] As the isoprene-based rubber, for example, those commonly used in the tire industry, such as isoprene rubber (IR) and natural rubber, can be used. Examples of natural rubber include: unmodified natural rubber (NR); and modified natural rubbers, such as epoxidized natural rubber (ENR), hydrogenated natural rubber (HNR), deproteinized natural rubber (DPNR), ultrapure natural rubber, grafted natural rubber, etc. These isoprene-based rubbers can be used alone or in combination of two or more.

[0039] The NR is not particularly limited, and those commonly used in the tire industry can be used, and examples include, for example, SIR20, RSS#3, TSR20, and the like.

[0040] When the isoprene rubber is compounded, the content of the isoprene rubber is preferably 5% by mass or more, more preferably 10% by mass or more, further preferably 20% by mass or more, and particularly preferably 30% by mass or more, based on 100% by mass of the rubber component, from the viewpoint of breaking strength. On the other hand, the upper limit of the isoprene rubber in the rubber component is not particularly limited, but is preferably 90% by mass or less, more preferably 85% by mass or less, further preferably 80% by mass or less, and particularly preferably 75% by mass or less.

[0041] (SBR)

[0042] SBR is not particularly limited, and examples include, for example, solution polymerization SBR (S-SBR), emulsion polymerization SBR (E-SBR), modified SBR (modified S-SBR, modified E-SBR), etc. Among these, S-SBR is preferred. Examples of modified SBR include: SBR modified at its end and / or main chain, modified SBR (condensate or modified SBR with branched structure, etc.) coupled with tin, silicon compounds, etc. In addition, as SBR, there is an oil-filled SBR and a non-oil-filled SBR that does not add filler oil to adjust flexibility, both of which can be used. For example, examples of SBR include SBR manufactured and sold by JSR Co., Ltd., Asahi Kasei Chemical Co., Ltd., and Zeon Co., Ltd. These SBRs can be used alone or in combination of two or more.

[0043] From the perspective of grip performance, the styrene content of SBR is preferably 15% by mass or more, more preferably 18% by mass or more, and further preferably 20% by mass or more. In addition, from the perspective of polymer dispersibility and fuel efficiency, the styrene content of SBR is preferably 60% by mass or less, more preferably 55% by mass or less, and further preferably 50% by mass or less. In addition, in this specification, the styrene content of SBR is expressed by 1 The results were calculated based on H-NMR measurements.

[0044] When SBR is compounded, from the perspective of wear resistance, the content of SBR is preferably 5% by mass or more, more preferably 10% by mass or more, further preferably 15% by mass or more, and particularly preferably 20% by mass or more, based on 100% by mass of the rubber component. In addition, the upper limit of the SBR content in the rubber component is not particularly limited, but is preferably 90% by mass or less, more preferably 85% by mass or less, further preferably 80% by mass or less, and particularly preferably 75% by mass or less.

[0045] (BR)

[0046] BR is not particularly limited, and for example, those commonly used in the tire industry can be used, such as BR having a cis-1,4 bond content (cis content) of less than 50% (low cis BR), BR having a cis-1,4 bond content of 90% or more (high cis BR), rare earth-based butadiene rubber synthesized using a rare earth element-based catalyst (rare earth-based BR), BR containing syndiotactic polybutadiene crystals (SPB-containing BR), and modified BR (high cis-modified BR and low cis-modified BR). These BRs can be used alone or in combination of two or more.

[0047] The cis 1,4 bond content of high cis BR is preferably 95% or more, more preferably 97% or more. When high cis BR is compounded, low temperature characteristics and wear resistance can be improved. For example, examples of high cis BR include high cis BR manufactured and sold by Zeon Co., Ltd., Ube Industries, Ltd., JSR Corporation, etc. For example, examples of rare earth BR include rare earth BR produced and sold by LANXESS, etc.

[0048] Examples of SPB-containing BR include those in which 1,2-syndiotactic polybutadiene crystals are chemically bonded to BR and dispersed therein, but do not include those in which crystals are simply dispersed in BR. For example, examples of SPB-containing BR include SPB-containing BR manufactured and sold by Ube Industries, Ltd., and the like.

[0049] Examples of modified BR include those obtained by adding a tin compound after polymerizing 1,3-butadiene with a lithium initiator, and those in which the modified BR molecule terminal has a tin-carbon bond (tin-modified BR), butadiene rubber having a condensed alkoxysilane compound at its active terminal (modified BR for silica), etc. For example, examples of such modified BR include tin-modified polymers manufactured by ZS Elastomer Co., Ltd., S-modified polymers (for modification of silica), etc.

[0050] When BR is compounded, from the viewpoint of wear resistance, the content of BR is preferably 5% by mass or more, more preferably 10% by mass or more, further preferably 15% by mass or more, further preferably 20% by mass or more, and particularly preferably 25% by mass or more, based on 100% by mass of the rubber component. The upper limit of the BR content in the rubber component is not particularly limited, but is preferably 90% by mass or less, more preferably 85% by mass or less, further preferably 80% by mass or less, and particularly preferably 75% by mass or less.

[0051] <Inorganic fiber materials>

[0052] The rubber composition according to the present invention contains an inorganic fiber material. By imparting anisotropy in addition to strength and rigidity to the inorganic fiber material oriented in the tire circumferential direction, a flexible response to input (vibration) from the vertical direction of the tire during rolling can be achieved; and by increasing the rigidity in the orientation direction (tire circumferential direction), the response to input during handling can be improved.

[0053] The inorganic fiber material that can be used in the present invention is not particularly limited, and examples include, for example, magnesium sulfate fiber, calcium silicate fiber, potassium titanate fiber, aluminum borate fiber, sepiolite, glass fiber, etc. Among these, one or more inorganic fiber materials selected from magnesium sulfate fiber, calcium silicate fiber, potassium titanate fiber, aluminum borate fiber and sepiolite are preferred, and magnesium sulfate fiber is more preferred. The above inorganic fiber materials can be used alone or in combination of two or more.

[0054] As magnesium sulfate fiber, alkaline magnesium sulfate fiber represented by MgSO4·5Mg(OH)2·3H2O is preferred. As calcium silicate fiber, calcium silicate fiber represented by 6CaO·6SiO2·H2O is preferred. As potassium titanate fiber, potassium titanate fiber represented by K2O·6TiO2 or K2O·8TiO2 is preferred. As aluminum borate fiber, aluminum borate fiber represented by 9Al2O3·2B2O3 is preferred. As sepiolite, Mg8SiO2 is preferred. 12 O 30 Sepiolite represented by (OH)4(H2O)4·8H2O.

[0055] As the inorganic fiber material, a commercially available material may be used, or a material produced by a known production method may be used. For example, specific examples of the inorganic fiber material include inorganic fiber materials produced and sold by Ube Materials Industries, Ltd., Otsuka Chemical Co., Ltd., Shikoku Chemical Industries, Ltd., Omi Mining Co., Ltd., and the like.

[0056] From the viewpoint of anisotropy of the rubber composition, the content of the inorganic fiber material is preferably 1.0 parts by mass or more, more preferably 1.5 parts by mass or more, further preferably 2.0 parts by mass or more, and particularly preferably 2.5 parts by mass or more relative to 100 parts by mass of the rubber component. Furthermore, from the viewpoint of the breaking strength of the rubber composition, the content of the inorganic fiber material is preferably 50 parts by mass or less, more preferably 45 parts by mass or less, further preferably 40 parts by mass or less, and particularly preferably 30 parts by mass or less.

[0057] From the perspective of the rigidity and processability of the rubber composition, the average diameter D (also referred to as the average fiber diameter or average width) of the inorganic fiber material is preferably 1.0 nm or more, more preferably 2.0 nm or more, and even more preferably 3.0 nm or more. In addition, from the perspective of the rigidity and breaking strength of the rubber composition, D is preferably 2000 nm or less, more preferably 1000 nm or less, even more preferably 500 nm or less, and particularly preferably 100 nm or less.

[0058] From the perspective of anisotropy of the rubber composition, the average length L (also referred to as average fiber length) of the inorganic fiber material is preferably 0.10 μm or more, more preferably 0.15 μm or more, further preferably 0.20 μm or more, and particularly preferably 0.50 μm or more. In addition, from the perspective of rigidity and breaking strength of the rubber composition, L is preferably 100 μm or less, more preferably 80 μm or less, further preferably 60 μm or less, and particularly preferably 40 μm or less.

[0059] Furthermore, in the present invention, the average diameter D and the average length L can be measured by image analysis of scanning electron micrographs, image analysis of transmission micrographs, analysis of X-ray scattering data, pore resistance method (Coulter principle), and the like.

[0060] From the viewpoint of anisotropy of the rubber composition, the aspect ratio L / D of the inorganic fiber material is preferably 2 or more, more preferably 4 or more, further preferably 6 or more, and particularly preferably 8 or more. Furthermore, from the viewpoint of the breaking strength of the rubber composition, L / D is preferably 1000 or less, more preferably 500 or less, further preferably 250 or less, and particularly preferably 100 or less.

[0061] <Coupling agent>

[0062] The rubber composition of the present invention contains a coupling agent. Inorganic fiber materials are difficult to disperse in the rubber component compared to fillers such as carbon black, but by compounding a coupling agent, the dispersibility of the inorganic fiber material can be improved, which can also improve anisotropy.

[0063] The coupling agent that can be used in the present invention is not particularly limited, and examples include a silane coupling agent that couples with silica and a rubber component, a carbon coupling agent that couples with carbon black and a rubber component, and the like.

[0064] (Silane coupling agent)

[0065] The silane coupling agent is not particularly limited, and silane coupling agents commonly used in combination with silica in the rubber industry can be used, for example, examples include: silane coupling agents having a mercapto group as described below; silane coupling agents having a thioether group, such as bis(3-triethoxysilylpropyl)disulfide and bis(3-triethoxysilylpropyl)tetrasulfide; silane coupling agents having a vinyl group, such as vinyltriethoxysilane and vinyltrimethoxysilane; silane coupling agents having an amino group, such as 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane and 3-(2-aminoethyl)aminopropyltriethoxysilane; glycidoxy silane coupling agents, such as γ-glycidoxypropyltriethoxysilane and γ-glycidoxypropyltrimethoxysilane; nitro silane coupling agents, such as 3-nitropropyltrimethoxysilane and 3-nitropropyltriethoxysilane; chlorine silane coupling agents, such as 3-chloropropyltrimethoxysilane and 3-chloropropyltriethoxysilane. Among these, silane coupling agents having thioether groups and / or silane coupling agents having mercapto groups are preferred, and silane coupling agents having thioether groups are more preferred. These silane coupling agents can be used alone or in combination of two or more.

[0066] Preferably, the silane coupling agent having a mercapto group is a compound represented by the following formula (1) and / or a compound containing a bonding unit A represented by the following formula (2) and a bonding unit B represented by the following formula (3).

[0067]

[0068] In the formula, R 101 , R 102 and R 103 Each independently represents an alkyl group having 1 to 12 carbon atoms, an alkoxy group having 1 to 12 carbon atoms, or -O-(R 111 -O) z -R 112 (z R 111 Each independently represents a divalent hydrocarbon group having 1 to 30 carbon atoms, R 112 represents an alkyl group having 1 to 30 carbon atoms, an alkenyl group having 2 to 30 carbon atoms, an aryl group having 6 to 30 carbon atoms or an aralkyl group having 7 to 30 carbon atoms; and z represents an integer of 1 to 30); R 104 It represents an alkylene group having 1 to 6 carbon atoms.

[0069]

[0070] In the formula, x represents an integer greater than 0; y represents an integer greater than 1; R 201 represents a hydrogen atom or an alkyl group having 1 to 30 carbon atoms, an alkenyl group having 2 to 30 carbon atoms or an alkynyl group having 2 to 30 carbon atoms, wherein the alkyl group, the alkenyl group and the alkynyl group are each optionally substituted by a halogen atom, a hydroxyl group or a carboxyl group; R 202 represents an alkylene group having 1 to 30 carbon atoms, an alkenylene group having 2 to 30 carbon atoms, or an alkynylene group having 2 to 30 carbon atoms; and R 201 and R 202 Can together form a ring structure.

[0071] For example, examples of the compound represented by the chemical formula (1) include 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 2-mercaptoethyltrimethoxysilane, 2-mercaptoethyltriethoxysilane, a compound represented by the following chemical formula (4) (Si363 manufactured by Evonik Degussa Co., Ltd.), etc. Among these, the compound represented by the following chemical formula (4) can be appropriately used. They can be used alone or in combination of two or more.

[0072]

[0073] For example, examples of the compound containing the bonding unit A represented by formula (2) and the bonding unit B represented by formula (3) include those manufactured and sold by Momentive Performance Materials, etc. These may be used alone or in combination of two or more.

[0074] (Carbon coupling agent)

[0075] The carbon coupling agent is not particularly limited, and examples include: tetrasulfides, such as bis(dimethylaminoethyl)tetrasulfide (DME) and bis(dimethylaminopropyl)tetrasulfide (DMP); benzimidazole compounds, such as 1,2-bis(benzimidazolyl-2)ethane (EBZ) and 1,4'-bis(mercaptobenzimidazolyl-2)butane (C4SBZ); pyrithione metal salts; etc. These carbon coupling agents can be used alone or in combination of two or more.

[0076] From the viewpoint of enhancing the dispersibility of the inorganic fiber material, the content of the coupling agent (preferably a silane coupling agent) is preferably 1.0 parts by mass or more, more preferably 1.5 parts by mass or more, and further preferably 2.0 parts by mass or more relative to 100 parts by mass of the rubber component. In addition, from the viewpoint of breaking strength, the content is preferably 40 parts by mass or less, more preferably 30 parts by mass or less, further preferably 20 parts by mass or less, and particularly preferably 15 parts by mass or less.

[0077] When the content of the inorganic fiber material relative to 100 parts by mass of the rubber component is defined as A (parts by mass), the content of the silica relative to 100 parts by mass of the rubber component is defined as B (parts by mass), and the content of the coupling agent (preferably a silane coupling agent) relative to 100 parts by mass of the rubber component is defined as X (parts by mass), A, B and X satisfy the following inequality (5):

[0078] 0.09A+0.08B≤X≤0.35A+0.08B (5)

[0079] <Packing>

[0080] In the above rubber composition, as fillers, those commonly used in conventional rubber industry, such as carbon black, silica, aluminum hydroxide, calcium carbonate, alumina, clay and talc can be compounded. Among these, the rubber composition preferably contains carbon black, more preferably contains carbon black and silica.

[0081] Since carbon black generates high heat during mixing, it is believed that carbon black promotes plasticization during mixing, and the inorganic fiber material reacts with the coupling agent, making the carbon black easy to disperse in the rubber matrix. At the same time, unlike the inorganic fiber material, since carbon black can obtain a reinforcing effect without anisotropy, it can impart the required minimum breaking strength in the transverse texture direction of the inorganic fiber. On the other hand, although the reinforcing effect of silica is not as good as that of carbon black and inorganic fiber materials, silica can flexibly exert the reinforcing effect, so it is believed that silica can reinforce the entire rubber matrix while ensuring flexibility in the transverse texture direction.

[0082] (Carbon Black)

[0083] There is no particular limitation on the carbon black, and those commonly used in the tire industry, such as GPF, FEF, HAF, ISAF and SAF, can be used. Specifically, N110, N115, N120, N125, N134, N135, N219, N220, N231, N234, N293, N299, N326, N330, N339, N343, N347, N351, N356, N358, N375, N539, N550, N582, N630, N642, N650, N660, N683, N754, N762, N765, N772, N774, N787, N907, N908, N990, N991 and the like can be appropriately used, and internally synthesized products and the like can also be appropriately used. These carbon blacks may be used alone or in combination of two or more.

[0084] From the perspective of weather resistance and reinforcement performance, the nitrogen adsorption specific surface area (N2SA) of carbon black is preferably 30 m 2 / g or more, more preferably 35m2 / g or more, more preferably 40m 2 In addition, from the perspective of dispersibility, fuel efficiency, fracture characteristics and durability, N2SA is preferably 250m 2 / g or less, more preferably 220m 2 In addition, the N2SA of carbon black in this specification is a value measured according to Method A of JIS K6217-2:2017 "Carbon black for rubber industry - Basic properties - Part 2: Determination of specific surface area - Nitrogen adsorption method - Single point method".

[0085] From the viewpoint of ensuring the anisotropy of the rubber composition without excessively strengthening the rubber network, the hexadecyltrimethylammonium bromide adsorption specific surface area (CTAB) of carbon black is preferably 180 m 2 / g or less, more preferably 165m 2 / g or less, more preferably 150m 2 On the other hand, from the perspective of reinforcement performance, the lower limit of the CTAB of carbon black is not particularly limited, but is preferably 30 m / s. 2 / g or more, more preferably 40m 2 / g or more, more preferably 50m 2 / g or more. Here, CTAB is a value related to the particle size of carbon black, which means that the larger the CTAB, the smaller the particle size of carbon black. In addition, the CTAB of carbon black in this specification is a value measured according to JIS K 6217-3:2001 "Carbon black for rubber industry-Basic properties-Part 3: Determination of specific surface area-CTAB adsorption method".

[0086] When carbon black is compounded, the content of carbon black is preferably 1 part by mass or more, more preferably 5 parts by mass or more, further preferably 10 parts by mass or more, and particularly preferably 15 parts by mass or more relative to 100 parts by mass of the rubber component from the viewpoint of weather resistance and reinforcement performance. In addition, from the viewpoint of fuel efficiency, the content of carbon black is preferably 100 parts by mass or less, more preferably 80 parts by mass or less, and further preferably 60 parts by mass or less.

[0087] (Silicon Dioxide)

[0088] Silica is not particularly limited, and those commonly used in the tire industry can be used, for example, silica prepared by a dry process (anhydrous silica) and silica prepared by a wet process (hydrous silica). Among these, hydrous silica prepared by a wet process is preferred because it has many silanol groups. These silicas can be used alone or in combination of two or more.

[0089] From the perspective of fuel efficiency and wear resistance, the nitrogen adsorption specific surface area (N2SA) of silica is preferably 140 m 2 / g or more, more preferably 150m 2 / g or more, more preferably 160m 2 / g or more, particularly preferably 170m 2 In addition, from the perspective of fuel efficiency and processability, N2SA is preferably 350m 2 / g or less, more preferably 300m 2 / g or less, more preferably 250m 2 In addition, the N2SA of silica in this specification is a value measured by the BET method according to ASTM D3037-93.

[0090] When silica is compounded, the content of silica is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, further preferably 15 parts by mass or more, and particularly preferably 20 parts by mass or more relative to 100 parts by mass of the rubber component from the viewpoint of fuel efficiency. In addition, from the viewpoint of processability, the content of silica is preferably 110 parts by mass or less, more preferably 100 parts by mass or less, further preferably 90 parts by mass or less, and particularly preferably 80 parts by mass or less.

[0091] From the viewpoint of reinforcement performance, the total content of silica and carbon black is preferably 20 parts by mass or more, more preferably 25 parts by mass or more, further preferably 30 parts by mass or more, and particularly preferably 35 parts by mass or more, relative to 100 parts by mass of the rubber component. In addition, from the viewpoint of processability, the total content of silica and carbon black is preferably 200 parts by mass or less, more preferably 170 parts by mass or less, further preferably 150 parts by mass or less, and particularly preferably 130 parts by mass or less.

[0092] The content of silica in the total content of silica and carbon black is preferably 50% or more, more preferably 70% or more, and even more preferably 80% or more.

[0093] The content of the inorganic fiber material in the total content of the inorganic fiber material, silica and carbon black is preferably 5% by mass or more, more preferably 8% by mass or more. This makes it easier to obtain the anisotropic effect of the inorganic fiber material. On the other hand, the content of the inorganic fiber material in the total content of the inorganic fiber material, silica and carbon black is preferably 30% by mass or less, more preferably 25% by mass or less, and further preferably 20% by mass or less. This allows the rubber phase to be reinforced only in the direction of the grain, allowing the strength in the transverse grain direction to be prevented from becoming very weak.

[0094] (Other compounding agents)

[0095] In addition to the above-mentioned components, rubber composition can also suitably comprise conventional and commonly used compounding agents in the tire industry, such as plasticizers, waxes, antioxidants, stearic acid, zinc oxide, vulcanizing agents (such as sulphur), vulcanization accelerators etc. In these, rubber composition preferably comprises plasticizers. By comprising plasticizers, the viscosity of rubber is reduced during mixing, so that the inorganic fiber material is easy to disperse, so anisotropy and breaking strength tend to be improved. The example of plasticizers includes such as oil, resin component, liquid rubber etc.

[0096] For example, examples of the oil include mineral oil (eg, aromatic oil), process oil, paraffin oil, etc. Among these, process oils are preferably used because they can reduce the burden on the environment.

[0097] When oil is compounded, the content of the oil is preferably 1 part by mass or more, more preferably 3 parts by mass or more, further preferably 5 parts by mass or more, and particularly preferably 7 parts by mass or more relative to 100 parts by mass of the rubber component from the viewpoint of processability. In addition, from the viewpoint of wear resistance, the content of the oil is preferably 80 parts by mass or less, more preferably 70 parts by mass or less, further preferably 60 parts by mass or less, and particularly preferably 50 parts by mass or less. In addition, in this specification, the content of the oil also includes the amount of oil contained in the oil-extended rubber.

[0098] The resin component is not particularly limited, and examples include petroleum resins commonly used in the tire industry, terpene resins, rosin resins, phenolic resins, etc. Examples of petroleum resins include C5-based petroleum resins, aromatic petroleum resins, C5-C9-based petroleum resins, etc. These resin components can be used alone or in combination of two or more.

[0099] In this specification, "C5-based petroleum resin" refers to a resin obtained by polymerizing a C5 fraction. Examples of C5 fractions include, for example, petroleum fractions having 4 to 5 carbon atoms, such as cyclopentadiene, pentene, pentadiene, and isoprene. As the C5-based petroleum resin, dicyclopentadiene resin (DCPD resin) can be appropriately used.

[0100] In this specification, "aromatic petroleum resin" refers to a resin polymerized from a C9 fraction, and can be hydrogenated or modified. For example, examples of C9 fractions include petroleum fractions corresponding to 8 to 10 carbon atoms, such as vinyl toluene, alkyl styrene, indene and methyl indene. As specific examples of aromatic petroleum resins, for example, coumarone indene resin, coumarone resin, indene resin and aromatic vinyl resins can be appropriately used. As aromatic vinyl resins, preferably a homopolymer of α-methylstyrene or styrene or a copolymer of α-methylstyrene and styrene, more preferably a copolymer of α-methylstyrene and styrene, because it is economical, easy to process, and excellent in heat generation. As aromatic vinyl resins, for example, those purchased from Kraton, Eastman Chemical Company, etc. can be used.

[0101] In this specification, "C5-C9-based petroleum resin" refers to a resin obtained by copolymerizing a C5 fraction and a C9 fraction, and may be hydrogenated or modified. Examples of the C5 fraction and the C9 fraction include the above-mentioned petroleum fractions. As the C5-C9-based petroleum resin, for example, those available from Tosoh Corporation, Zibo Luhua Hongjin New Materials Co., Ltd., etc. can be appropriately used.

[0102] Examples of terpene resins include: polyterpene resins composed of at least one selected from terpene compounds (e.g., α-pinene, β-pinene, limonene, and dipentene); aromatic modified terpene resins made from terpene compounds and aromatic compounds; terpene phenol resins made from terpene compounds and phenolic compounds; and those in which these terpene resins are hydrogenated (hydrogenated terpene resins). For example, examples of aromatic compounds used as raw materials for aromatic modified terpene resins include styrene, α-methylstyrene, vinyltoluene, divinyltoluene, etc. For example, examples of phenolic compounds used as raw materials for terpene phenol resins include phenol, bisphenol A, cresol, xylenol, etc.

[0103] For example, examples of the rosin-based resin include, but are not particularly limited to, natural resin rosin and rosin-modified resins obtained by modifying it through hydrogenation, disproportionation, dimerization, esterification, or the like.

[0104] Examples of the phenolic resin include, but are not particularly limited to, phenolic resins, alkylphenolic resins, alkylphenolacetylene resins, oil-modified phenolic resins, and the like.

[0105] When the resin component is compounded, the content of the resin component is preferably 1 part by mass or more, more preferably 3 parts by mass or more, and further preferably 5 parts by mass or more relative to 100 parts by mass of the rubber component. In addition, the content of the resin component is preferably 50 parts by mass or less, more preferably 40 parts by mass or less, and further preferably 20 parts by mass or less.

[0106] The liquid rubber is not particularly limited as long as it is a liquid polymer at normal temperature (25° C.), and examples include, for example, liquid butadiene rubber (liquid BR), liquid styrene-butadiene rubber (liquid SBR), liquid isoprene rubber (liquid IR), liquid styrene-isoprene rubber (liquid SIR), liquid farnesene rubber, etc. These liquid rubbers may be used alone or in combination of two or more.

[0107] When liquid rubber is compounded, the content of the liquid rubber is preferably 1 part by mass or more, more preferably 3 parts by mass or more, and further preferably 5 parts by mass or more relative to 100 parts by mass of the rubber component. In addition, the content of the liquid rubber is preferably 50 parts by mass or less, more preferably 40 parts by mass or less, and further preferably 20 parts by mass or less.

[0108] The content of the plasticizer (the total amount of multiple plasticizers when used in combination) is preferably 1 part by mass or more, more preferably 3 parts by mass or more, further preferably 5 parts by mass or more, and particularly preferably 7 parts by mass or more relative to 100 parts by mass of the rubber component. In addition, the content of the plasticizer is preferably 90 parts by mass or less, more preferably 70 parts by mass or less, further preferably 50 parts by mass or less, and particularly preferably 30 parts by mass or less. When the content of the plasticizer exceeds 90 parts by mass, the entire rubber matrix will be softened by the plasticizer, and sufficient reinforcement performance of the inorganic fiber material cannot be obtained, so anisotropy and breaking strength tend to decrease.

[0109] When wax is compounded, the content of the wax is preferably 0.5 parts by mass or more, more preferably 1.0 parts by mass or more, and further preferably 1.5 parts by mass or more relative to 100 parts by mass of the rubber component from the viewpoint of weather resistance of the rubber. In addition, from the viewpoint of preventing whitening of the tire due to blooming, the content of the wax is preferably 10 parts by mass or less, and more preferably 5 parts by mass or less.

[0110] For example, examples of antioxidants include, but are not particularly limited to, amine compounds, quinoline compounds, quinone compounds, phenolic compounds, and imidazole compounds, as well as antioxidants such as metal carbamates, preferably phenylenediamine antioxidants, such as N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine, N-isopropyl-N'-phenyl-p-phenylenediamine, N,N'-diphenyl-p-phenylenediamine, N,N'-di-2-naphthyl-p-phenylenediamine, N-cyclohexyl-N'-phenyl-p-phenylenediamine, N,N'-bis(1-methylbutyl)-N'-phenyl-p-phenylenediamine, p-phenylenediamine, N,N'-bis(1,4-dimethylpentyl)-p-phenylenediamine, N,N'-bis(1-ethyl-3-methylpentyl)-p-phenylenediamine, N-4-methyl-2-pentyl-N'-phenyl-p-phenylenediamine, N,N'-diaryl-p-phenylenediamine, hindered diaryl-p-phenylenediamine, phenylhexyl-p-phenylenediamine and phenyloctyl-p-phenylenediamine, and quinoline antioxidants such as 2,2,4-trimethyl-1,2-dihydroquinoline polymers and 6-ethoxy-2,2,4-trimethyl-1,2-dihydroquinoline. These antioxidants can be used alone or in combination of two or more.

[0111] When an antioxidant is compounded, from the viewpoint of the ozone crack resistance of the rubber, the content of the antioxidant is preferably 0.5 parts by mass or more, more preferably 1.0 parts by mass or more, and further preferably 1.5 parts by mass or more relative to 100 parts by mass of the rubber component. In addition, from the viewpoint of abrasion resistance and wet grip performance, the content of the antioxidant is preferably 10 parts by mass or less, and more preferably 5 parts by mass or less.

[0112] When stearic acid is blended, the content of stearic acid is preferably 0.5 parts by mass or more, more preferably 1.0 parts by mass or more, and further preferably 1.5 parts by mass or more relative to 100 parts by mass of the rubber component from the viewpoint of processability. In addition, from the viewpoint of vulcanization rate, the content of stearic acid is preferably 10 parts by mass or less, and more preferably 5 parts by mass or less.

[0113] When zinc oxide is compounded, the content of zinc oxide is preferably 0.5 parts by mass or more, more preferably 1.0 parts by mass or more, and further preferably 1.5 parts by mass or more relative to 100 parts by mass of the rubber component from the viewpoint of processability. In addition, from the viewpoint of wear resistance, the content of zinc oxide is preferably 10 parts by mass or less, and more preferably 5 parts by mass or less.

[0114] Sulfur is suitably used as a vulcanizing agent. As sulfur, powdered sulfur, oil-treated sulfur, precipitated sulfur, colloidal sulfur, insoluble sulfur, highly dispersible sulfur, etc. can be used.

[0115] When sulfur (as a vulcanizing agent) is compounded, the sulfur content is preferably 0.5 parts by mass or more, more preferably 1.0 parts by mass or more, and further preferably 1.5 parts by mass or more relative to 100 parts by mass of the rubber component from the viewpoint of ensuring a sufficient vulcanization reaction and obtaining good grip performance and wear resistance. In addition, from the viewpoint of preventing deterioration, the sulfur content is preferably 5.0 parts by mass or less, more preferably 4.5 parts by mass or less, and further preferably 4.0 parts by mass or less.

[0116] For example, examples of the vulcanizing agent other than sulfur include: a vulcanizing agent containing a sulfur atom, such as TACKIROL V-200 manufactured by Taoka Chemical Co., Ltd., DURALINK HTS (sodium hexamethylene-1,6-dithiosulfate dihydrate) manufactured by Flex, and KA9188 (1,6-bis(N,N'-dibenzylthiocarbamoyldisulfide)hexane) manufactured by LANXESS; an organic peroxide such as diisopropyl peroxide, etc.

[0117] For example, examples of the vulcanization accelerator include, but are not particularly limited to, sulfenamide-based vulcanization accelerators, thiazole-based vulcanization accelerators, thiuram-based vulcanization accelerators, thiourea-based vulcanization accelerators, guanidine-based vulcanization accelerators, dithiocarbamic acid-based vulcanization accelerators, aldehydeamine-based or aldehydeamine-based vulcanization accelerators, imidazoline-based vulcanization accelerators, and xanthate-based vulcanization accelerators; among these, sulfenamide-based vulcanization accelerators and guanidine-based vulcanization accelerators are preferred from the viewpoint that the desired effect can be more appropriately obtained, and a combination of the two is more preferred.

[0118] Examples of sulfenamide-based vulcanization accelerators include: CBS (N-cyclohexyl-2-benzothiazolyl sulfenamide), TBBS (N-tert-butyl-2-benzothiazolyl sulfenamide), N-oxyethylene-2-benzothiazolyl sulfenamide, N,N'-diisopropyl-2-benzothiazolyl sulfenamide, N,N-dicyclohexyl-2-benzothiazolyl sulfenamide, etc. Examples of thiazole-based vulcanization accelerators include: 2-mercaptobenzothiazole, dibenzothiazolyl disulfide, etc. Examples of thiuram-based vulcanization accelerators include tetramethylthiuram monosulfide, tetramethylthiuram disulfide, tetrabenzylthiuram disulfide (TBzTD), etc. Examples of guanidine-based vulcanization accelerators include 1,3-diphenylguanidine (DPG), di-o-tolylguanidine, o-tolylbiguanide, etc. These vulcanization accelerators can be used alone or in combination of two or more.

[0119] When a vulcanization accelerator is compounded, the content of the vulcanization accelerator is preferably 0.5 parts by mass or more, more preferably 1.0 parts by mass or more, and further preferably 1.5 parts by mass or more, relative to 100 parts by mass of the rubber component. In addition, the content of the vulcanization accelerator is preferably 8 parts by mass or less, more preferably 7 parts by mass or less, and further preferably 6 parts by mass or less, relative to 100 parts by mass of the rubber component. When the content of the vulcanization accelerator is within the above range, breaking strength and elongation tend to be ensured.

[0120] [Rubber composition and method for producing a tire]

[0121] The rubber composition of the present invention can be produced by a known method, for example, the rubber composition of the present invention can be produced by kneading the components except the vulcanizing agent and the vulcanization accelerator among the above components with a known kneading machine (e.g., Banbury mixer, kneading machine, and open roll mill) used in general rubber industry, then adding the vulcanizing agent and the vulcanization accelerator to the mixture to further knead it, and then vulcanizing it, etc. For example, in the kneading step, kneading is performed at 80° C. to 170° C. for 1 to 30 minutes; in the vulcanization step, vulcanization is performed at 130° C. to 190° C. for 3 to 20 minutes.

[0122] It is believed that the rubber composition of the present invention can realize the flexible response to the input (vibration) from the vertical direction of the tire during rolling by orienting the inorganic fiber in the tire circumferential direction, and the response to the input during handling can be improved by increasing the rigidity of the orientation direction (tire circumferential direction). Therefore, it can be appropriately used for continuous parts on the tire circumference, such as tread running surface, tread base, sidewall, sidewall inner layer, inner liner, strip apex rubber, bead apex rubber, lap apex rubber, bead reinforcing layer, isolation layer and insert, and it is believed that similar effects can be obtained in any case. Among these, it is suitable for use as a rubber composition for tire internal parts (such as tread base, sidewall inner layer, inner liner, strip apex rubber, bead apex rubber, bead reinforcing layer, isolation layer and insert). When the rubber composition of the present invention is used as such a tire internal part, the elasticity (responsiveness) of the tire in the rolling direction can be improved while maintaining buffering performance, so it is believed that handling stability and ride comfort can be improved.

[0123] Furthermore, in this specification, "inner components" are not limited to the above components, but shall refer to tire components other than components forming the outer surface when the tire is mounted on a rim and filled with air.

[0124] The tire of the present invention can be manufactured by conventional methods using the above-mentioned rubber composition. That is, the unvulcanized rubber composition (the above-mentioned components are compounded with the rubber component as required) is extruded into the shape of the corresponding tire component to obtain a rubber composition in which the inorganic fiber material is oriented in the texture direction. Then, the above-mentioned rubber composition is attached to other tire components on a tire molding machine so that the inorganic fiber material is oriented in the tire circumferential direction, and the mixture is molded to form an unvulcanized tire by conventional methods, and the unvulcanized tire is heated and pressurized in a vulcanizer to make a tire. The tire of the present invention can be a pneumatic tire or a non-pneumatic tire. In addition, it is suitable for racing tires, passenger car tires, large passenger car tires, large SUV tires or motorcycle tires, and can also be used as summer tires, winter tires or their studless anti-skid tires.

[0125] Example

[0126] Although the present invention will be described based on the embodiments, the present invention is not limited to the embodiments.

[0127] Various chemicals used in Examples and Comparative Examples are shown below.

[0128] NR:TSR20

[0129] BR: Ubepol BR150B manufactured by Ube Industries, Ltd. (cis content: 97%)

[0130] SBR1: Tufdene 3830 manufactured by Asahi Kasei Corporation (unmodified S-SBR, styrene content: 32% by mass, oil-extended product having an oil content of 37.5 parts by mass relative to 100 parts by mass of the rubber component)

[0131] SBR2: Asaprene 1205 manufactured by Asahi Kasei Corporation (unmodified S-SBR, styrene content: 25% by mass)

[0132] Carbon black: Show Black N220 (CTAB: 110m 2 / g, N2SA: 111m 2 / g)

[0133] Silicon dioxide: Ultrasil (registered trademark) VN3 (N2SA: 175m 2 / g)

[0134] Inorganic fiber material 1: MOS-HIGE manufactured by Ube Materials Industries, Ltd. (basic magnesium sulfate fiber, average fiber diameter: 500-1000 nm, average fiber length: 8-30 μm)

[0135] Inorganic fiber material 2: sepiolite (average fiber diameter: 5-30 nm, average fiber length: 0.2-2.0 μm)

[0136] Inorganic fiber material 3: Xonohige manufactured by Ube Materials Industries, Ltd. (calcium silicate fiber, average fiber diameter: 100-500 nm, average fiber length: 1-5 μm)

[0137] Silane coupling agent: Si69 (bis(3-triethoxysilylpropyl)tetrasulfide) manufactured by Evonik Degussa GmbH

[0138] Oil: Operating oil X-140 manufactured by INNOS Co., Ltd.

[0139] Antioxidant: OZONONE 6C (N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine) manufactured by Seiko Chemical Co., Ltd.

[0140] Stearic acid: Camellia stearic acid manufactured by NOF Corporation

[0141] Zinc oxide: Zinc oxide No. 1 manufactured by Mitsui Mining and Smelting Co., Ltd.

[0142] Wax: OZOACE 0355 manufactured by Nippon Seiro Co., Ltd.

[0143] Sulfur: Powdered sulfur manufactured by Tsurumi Chemical Co., Ltd.

[0144] Vulcanization accelerator 1: SOXINOL CZ (N-cyclohexyl-2-benzothiazolylsulfenamide) manufactured by Sumitomo Chemical Co., Ltd.

[0145] Vulcanization accelerator 2: SOXINOL D (1,3-diphenylguanidine) manufactured by Sumitomo Chemical Co., Ltd.

[0146] (Examples and Comparative Examples)

[0147] According to the compounding formula shown in Table 1 and Table 2, a Banbury mixer manufactured by Kobe Steel was used to knead the materials other than sulfur and vulcanization accelerator to obtain a kneaded product. Then, sulfur and vulcanization accelerator were added to the obtained kneaded product, and the mixture was kneaded using an open roll mill to obtain an unvulcanized rubber composition. A sheet with a thickness of 0.5 mm was prepared from the obtained unvulcanized rubber composition using an open roll mill. The obtained unvulcanized rubber sheets were stacked to form a 1.5 mm sheet, which was press-vulcanized at 150°C for 15 minutes to prepare a test vulcanized rubber sheet. In addition, the above-mentioned unvulcanized rubber composition was extruded into the shape of a sidewall inner layer using an extruder equipped with a suction nozzle of a predetermined shape to obtain a sidewall inner layer in which the inorganic fiber material was oriented in the texture direction. Then, the sidewall inner layer is attached to other tire components on a tire forming machine so that the inorganic fiber material is oriented in the circumferential direction of the tire to form an unvulcanized tire. The unvulcanized tire is pressurized and vulcanized at 170°C for 12 minutes to form a tire (size: 205 / 65R15).

[0148] <Anisotropy test>

[0149] The above-mentioned vulcanized rubber sheet was punched in the grain direction (the direction of rotation of the roller when manufacturing the unvulcanized rubber sheet before vulcanization) using a JIS No. 3 dumbbell, and the tensile stress (M100a) at 100% elongation in the grain direction was measured under the condition of a tensile speed of 500 mm / min according to JIS K 6251:2017. Similarly, the vulcanized rubber sheet was punched in the transverse grain direction (the direction perpendicular to the direction of rotation of the roller when manufacturing the unvulcanized rubber sheet before vulcanization) using a JIS No. 3 dumbbell, and the tensile stress (M100b) at 100% elongation in the transverse grain direction was measured under the condition of a tensile speed of 500 mm / min according to JIS K 6251:2017. Then, the modulus ratio (M100a / M100b) was calculated, which is described in Tables 1 and 2.

[0150] <Tensile test>

[0151] Using a No. 3 dumbbell-shaped test piece composed of a vulcanized rubber composition, the elongation at break EB (%) and the tensile strength TB (MPa) value of the vulcanized rubber sheet were measured according to JIS K 6251: 2017. The breaking strength was calculated from the obtained values ​​by the following formula and expressed as an index (breaking strength index) when the reference comparative example (Comparative Example 1 in Table 1, Comparative Example 3 in Table 2, the same below) was set to 100. The results show that the larger the index, the better the breaking strength.

[0152] Breaking strength = EB × TB / 2

[0153] <Evaluation of handling stability and ride comfort>

[0154] The prototype tire was mounted on a standard rim (size = 16 × 6.5J) and filled with air to set the internal pressure to 210 kPa. This tire was mounted on a car with a displacement of 2000cc. The car was driven on a test track with an asphalt surface, and the test driver conducted a sensory evaluation of the ride comfort and control stability (handling stability) during the operation. The evaluation was based on a 10-point system, in which a relative evaluation was performed with a reference comparative example of 6.0 points. The results showed that the higher the score, the better the handling stability and ride comfort.

[0155] Table 1

[0156]

[0157] Table 2

[0158]

[0159] It can be seen from the results in Tables 1 and 2 that the rubber composition of the present invention comprising an inorganic fiber material and a coupling agent can achieve both high breaking strength and anisotropy. In addition, it can be seen that the tire of the present invention (having a tire inner component formed of the rubber composition) has well-balanced improved ride comfort and handling stability.

Claims

1. A tire internal component, which is formed of a rubber composition comprising a rubber component, an inorganic fiber material oriented in the tire circumferential direction, and a coupling agent, in, The inorganic fiber material is one or more inorganic fiber materials selected from magnesium sulfate fiber, calcium silicate fiber, potassium titanate fiber, aluminum borate fiber and glass fiber, The inorganic fiber material has an average diameter D of 1.0 to 2000 nm and an average length L of 0.10 to 80 μm.

2. The tire interior component according to claim 1, wherein: The rubber composition has a ratio (M100a / M100b) of a 100% modulus M100a in a grain direction to a 100% modulus M100b in a transverse grain direction of 1.10 or more.

3. The tire interior component according to claim 1 or 2, wherein: The rubber composition further includes carbon black.

4. The tire interior component according to claim 1 or 2, wherein: The rubber composition further includes a plasticizer.

5. The tire interior component according to claim 1 or 2, wherein: The rubber component includes isoprene-based rubber.

6. The tire interior component according to claim 1 or 2, wherein: The coupling agent is a silane coupling agent.

7. The tire interior component according to claim 1 or 2, wherein: The rubber composition includes 1 to 40 parts by mass of the coupling agent relative to 100 parts by mass of the rubber component.

8. The tire interior component according to claim 1 or 2, wherein: The coupling agent is a silane coupling agent having a thioether group.

9. The tire interior component according to claim 1 or 2, wherein: The rubber composition further comprises carbon black, wherein the carbon black has a cetyltrimethylammonium bromide adsorption specific surface area (CTAB) of 180 m 2 / g or less.

10. The tire interior component according to claim 1 or 2, wherein: The rubber composition contains 1 to 50 parts by mass of an inorganic fiber material having an average diameter D of 3.0 to 1000 nm, an average length L of 0.50 to 60 μm, and an aspect ratio L / D of 2 to 1000, relative to 100 parts by mass of the rubber component.

11. The tire interior component according to claim 1 or 2, wherein: The inorganic fiber material is one or more inorganic fiber materials selected from magnesium sulfate fiber, calcium silicate fiber, potassium titanate fiber and aluminum borate fiber.

12. A tire comprising the tire internal component according to any one of claims 1 to 11.

13. The tire according to claim 12, wherein: The tire is a tire for a passenger car.

Citation Information

Patent Citations

  • Semiconductor device

    JP1981091463A

  • Manufacturing method for studless tire and its tread

    JP2004034744A

  • Rubber composition for tire, and pneumatic tire

    JP2012087188A